IDNLearn.com: Your trusted source for finding accurate and reliable answers. Discover trustworthy solutions to your questions quickly and accurately with help from our dedicated community of experts.
Sagot :
Ok so .. the first answer is
-2x + 18 =2
Move the constant to the right
-2x =2 - 18
Calculate the difference
-2x = -16
Divide both sides of the equation by -2
And that’s how I got x=8
The other one is x - 6y = -4
X= 6y - 4
Move the variable to the left hand side by adding it’s opposite to both sides
X - 6y = 6y - 4 - 6y
Since two opposites add up to zero,remove them from the expression
And that’s how x - 6y = -4
-2x + 18 =2
Move the constant to the right
-2x =2 - 18
Calculate the difference
-2x = -16
Divide both sides of the equation by -2
And that’s how I got x=8
The other one is x - 6y = -4
X= 6y - 4
Move the variable to the left hand side by adding it’s opposite to both sides
X - 6y = 6y - 4 - 6y
Since two opposites add up to zero,remove them from the expression
And that’s how x - 6y = -4
We appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. Thank you for trusting IDNLearn.com with your questions. Visit us again for clear, concise, and accurate answers.